AUTOMATIC CONTROL SYSTEM SWITCHING ROADWAY LIGHTING - Agus Trimuji Susilo; Lingga Hermanto Drs. MM (Jurnal Sistem Komputer, 2002)
Lack of attention to the information officer street lights, cause is not exactly the timewhen the blame lights street lighting street - the street in this city protocol. And whenit was already dark, the lights had not lit, so it can harm the users of the road. Werecommend that when it got bright lights - the lights switched off late, so muchelectricity is wasted with nothing - nothing.Given the problems above, the automatic switching is required that can control all thelights - the existing lighting on the road - the road protocol. In this case, the authoruses a light sensor (LDR) as an automatic controller roadway lighting that uses lightintensity to give a signal - a signal to other control components.